2021
DOI: 10.1002/anie.202114598
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenation of Nitrous Oxide and Nitro Compounds Using Bis(N‐Heterocyclic Silylene)Amido Iron Complexes as Catalysts

Abstract: Herein, we report the efficient degradation of N 2 O with a well-defined bis(silylene)amido iron complex as catalyst. The deoxygenation of N 2 O using the iron silanone complex 4 as a catalyst and pinacolborane (HBpin) as a sacrificial reagent proceeds smoothly at 50 °C to form N 2 , H 2 , and (pinB) 2 O. Mechanistic studies suggest that the ironsilicon cooperativity is the key to this catalytic transformation, which involves N 2 O activation, H atom transfer, H 2 release and oxygenation of the boron sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…Addition ether (B-O-B) was also observed. [18] IR analysis of the reaction mixture displayed an identical ν(C-O) stretching frequency at 1828 cm -1 confirming the formation of Co(0) carbonyl complex 4. Scheme 4.…”
Section: Resultsmentioning
confidence: 70%
“…Addition ether (B-O-B) was also observed. [18] IR analysis of the reaction mixture displayed an identical ν(C-O) stretching frequency at 1828 cm -1 confirming the formation of Co(0) carbonyl complex 4. Scheme 4.…”
Section: Resultsmentioning
confidence: 70%
“…This is an unprecedented catalytic activation of N 2 O by main group elements, 51 53 which performs comparable or beyond TM deoxygenation catalysis. 54 57 Albeit restricted to HBpin, this work reveals the potential of Bi catalysts for O -atom transfer (OAT), which can eventually be applied to organic substrates in catalytic oxidative transformations.…”
Section: Low-valent Catalysismentioning
confidence: 99%
“…[36] Very recently, Mo et al reported a silanone-iron complex with an intramolecular Si=O!Fe interaction. [37] Reaction of 25 with three equivalents of PNO at 80 °C proceeded via the oxygenation of the silanone and trimethylsilyl migration to form the dioxo(disiloxanoxy)tungsten complex 29 (Scheme 7). [32] Treatment of 25 with two equivalents of MeOH at 25 °C led to the formation of Mes 2 Si(OMe)OH (30), MeOSiMe 3 (31), and [Cp*W(CO) 2 ] 2 (32), in contrast, 25 reacted with H 2 O to give mainly Mes 2 Si(OH)(OSiMe 3 ) (33).…”
Section: Silacarbonyl Compounds With a Four-coordinate Silicon Centermentioning
confidence: 99%
“…[34] The molybdenum silanone complex 26 slowly evolved at 25 °C to generate DMAP-coordinated molybdenum carbonyl complex 34, while 27 decomposed in the presence of PMe 3 at 25 °C to afford the disiloxanoxy(dicarbonyl) complex 35 (Scheme 8). [33] The reaction of 26 with two equivalents of MeOH at 25 °C yielded 30, 31, [Cp*Mo(CO) 2 ] 2 (36) and 34, however, treatment of 26 with H 2 O generated the hydrolysis product Mes 2 Si(OH) 2 (37) as the main product. [34] When 28 was employed to react with DMAP, 25 was generated via the replacement of pyridine with DMAP, suggest- ing the more strong electron-donating ability of DMAP compared to pyridine (Scheme 9).…”
Section: Silacarbonyl Compounds With a Four-coordinate Silicon Centermentioning
confidence: 99%
See 1 more Smart Citation